EKONOMI ISLAM SOLUSI BAGI SISTEM EKONOMI - Usman, Ermawati (State Institute of Islamic Studies (IAIN) Palu, 2006)
This article aims to introduce Islamic economics system and to find out a solution for economics system implemented by most states in the world. The intended economics systems is that Islamic economics as an alternative economics system besides capitalist system of economy and socialist system of economy. The emergence of Islamic economics system has provided a new solution for restoration of world economy. There have been many countries that concern to Islamic economics system and made it as their system of economy albeit being limited to the finance affairs. However, it indicates a beautiful beginning for the reawakening of economics system ever emerged in great Islamic civilization.Â Kata Kunci: Â Ekonomi Islam, sistem ekonomi, kapitalis, sosialis